Role of lactate dehydrogenase A in malignant hematological diseases - MO Yuzhen, CHEN Tingting, ZHOU Hebing (Jichu yixue yu linchuang)
Lactate dehydrogenase A (LDHA) is an important enzyme involved in the anaerobic glycolysis of cells, catalyzing the conversion of pyruvate to lactate and participating in processes such as tumor proliferation, migration, invasion, and the regulation of the tumor microenvironment. High expression levels of LDHA are often indicative of disease progression and poor prognosis in malignant hematological diseases. The expression of LDHA in malignant hematological diseases is closely associated with various molecules, including HIF-1, microRNAs and c-Myc, as well as signaling pathways like PI3K/AKT/GSK3, USP1/PLK1/LDHA and Fbw7/LDHA/lactate/miR-223. Meanwhile,the progression of malignant hematological conditions facilitated by LDHA primarily occurs through the regulation of energy metabolism via glycolytic pathways.